Korelasi Pengetahuan Komunitas Pasar terhadap Penggunaan Rhodamin B pada Pangan di Pasar Tradisional Bangka Belitung - Ma'rifah Ebtasari; Ika Kartika (Eruditio : Indonesia Journal of Food and Drug Safety, 2025)
Food safety, especially the use of rhodamine B as a coloring agent, is an important public health issue. Public knowledge regarding the use of this substance is important, as it may influence consumption patterns. This research aims to determine the correlation between the level of market community knowledge and the use of rhodamine B in food products across six traditional markets on Bangka Belitung Island. Random surveys were conducted among buyers, traders, community groups, and market officers to assess market knowledge. To determine the rhodamine B content, selected samples, based on color, texture, and other risk factors, were tested using a rapid test kit. The survey results showed that the level of market community knowledge ranged from 59.38 – 100%. Of the 102 tests, 16 samples tested positive for rhodamine B. The positive samples were shrimp paste, apem, mutiara sago porridge, and ice cream cones. To determine the correlation, the two variables were tested using the Pearson correlation test in SPSS version 16. The test results showed a significance value of Sig. 0.078 > alpha 0.05 with a confidence level of 95%, which means no statistical correlation between the variables being compared. The study showed that a higher level of market community knowledge did not guarantee lower rhodamine B use, and vice versa. However, other factors that may influence rhodamine B use in food on Bangka Belitung Island warrant further study.